Tormentic Acid Ameliorates Hepatic Fibrosis in vivo by Inhibiting Glycerophospholipids Metabolism and PI3K/Akt/mTOR and NF-κB Pathways: Based on Transcriptomics and Metabolomics - Lin, Xing; Wei, Yuanyuan; Li, Yan; Xiong, Yuhua; Fang, Bin; Li, Cuiyu; Huang, Quanfang; Huang, Renbin; Wei, Jinbin (Frontiers in Pharmacology, 2022)
This study aimed to investigate the effects and underlying mechanisms of Tormentic acid (TA) on carbon tetrachloride (CCl4)-induced liver fibrosis in rats. The rats were intragastrically administered with 50% CCl4 for 9 weeks to induce hepatic fibrosis, followed by various agents for 6 weeks. Transcriptomic analysis was carried out to predict the potential targets, and then multiple examinations were performed to verify the prediction. The results showed that TA significantly alleviated liver injury and fibrosis, as evidenced by the ameliorative pathological tissue, low transaminase activity, and decreased collagen accumulation. Besides, TA markedly reduced hepatocyte apoptosis by regulating the expression of caspase-3 and Bcl-2 families. For the underlying mechanism, the transcriptomic analysis indicated that there were 2173 differentially expressed genes (DEGs) between the TA and model groups, which could enrich in the metabolic pathways (especially the glycerophospholipids metabolism) and the PI3K/Akt and NF-κB signaling pathways. Then, the metabolomics analysis verified that TA could regulate the glycerophospholipid metabolism pathway by moderating the possible biomarkers (including phosphatidylserine, phosphatidylethanolamine and phosphatidylcholine) through inhibiting the genes expression (including LPCAT4, PTDSS2, PLA2G2A and CEPT1). Moreover, further study confirmed that TA inhibited HSCs activation by blocking the PI3K/Akt/mTOR pathway and ameliorated inflammatory injury by inhibiting the NF-κB pathway. Interestingly, the bioinformatic analysis and the qPCR assay suggested that miR-200a might be the common target that TA controlled the metabolic and signaling pathways above. In conclusion, TA significantly alleviates liver fibrosis likely by enhancing miR-200a transcription and inhibiting the glycerophospholipid metabolism pathway and the PI3K/Akt/mTOR and NF-κB signaling pathways.